Oleuropein aglycone attenuates the pro-angiogenic phenotype of senescent fibroblasts: A functional study in endothelial cells. (February 2019) - Margheri, Francesca; Menicacci, Beatrice; Laurenzana, Anna; Del Rosso, Mario; Fibbi, Gabriella; Cipolleschi, Maria Grazia; Ruzzolini, Jessica; Nediani, Chiara; Mocali, Alessandra; Giovannelli, Lisa
Graphical abstract: Highlights: Senescent cells are characterized by the senescence-associated secretory phenotype. Oleuropein aglycone attenuates senescence-dependent pro-angiogenic microenvironment. Reduction of invasive activity and capillary morphogenesis by endothelial cells. Beneficial effects of Mediterranean diet against cancer and cardiovascular disease. Abstract: The "senescence-associated secretory phenotype" (SASP) supports a pro-tumoral and pro-angiogenic microenvironment through increased secretion of inflammatory and growth factors. We investigated oleuropein aglycone (OLE, 10 µM, 5 weeks) effect on capillary morphogenesis induced by MRC5 fibroblast SASP in mature (hMVEC) and progenitor (ECFC) endothelial cells. In senescent fibroblasts OLE reduced NFkB signaling and the expression of several SASP factors. The levels of IL-8 and VEGF were decreased in senescent fibroblast-conditioned medium collected after OLE treatment (CM senOLE) compared to that from untreated fibroblasts (CM sen). Pre-incubation with CMsen enhanced invasive activity and capillary morphogenesis in endothelial cells. This angiogenic phenotype was significantly attenuated upon pre-incubation with CM senOLE, along with reduced MMP-2, MMP-9 and uPA secretion by endothelial cells. In conclusion, OLE can modulate angiogenesis indirectly acting on local senescent fibroblasts, a new mechanism possibly contributing to the beneficial effects of the Mediterranean diet against cancer and cardiovascular diseases.